Investigation on chemical and structural properties of coal- and petroleum-derived pitches and implications on physico-chemical properties (solubility, softening and coking). (1st June 2019) - Russo, C.; Ciajolo, A.; Stanzione, F.; Tregrossi, A.; Oliano, M.M.; Carpentieri, A.; Apicella, B.
Graphical abstract: Highlights: Insights on pitch structure for guiding the production of tailored carbon materials. Correlation of pitch properties with their source. Match of several techniques for coal-tar and petroleum pitches characterization. Comparison of coal-tar and petroleum pitches characteristics and composition. Abstract: The structural properties and composition of pitches are particularly important for the optimization of pitch processing to high-value products and practical application. Because of their complexity, pitch analysis requires both chemical and spectroscopic tools, as those applied in the present work to coal and petroleum-derived pitch samples. In particular, a large variety of methods, including chromatography, elemental analysis, thermogravimetry, mass spectrometry, UV–Visible and FTIR spectroscopy, was applied for evidencing the different characteristics of commercial solid pitch derived from petroleum and coal. The interrelation among some pitch properties was investigated by analyzing petroleum and coal-derived pitches having different softening points and volatility. It was observed that properties as the softening point and the coking yield are mainly related to the pitch volatility rather than on the pitch source (coal or petroleum), whereas some other features as the solubility and the oxidation reactivity of coke produced appeared correlated with the source characteristics.